Pengaruh Tata Ruang Toko, Variasi Produk, Desain Produk Dan Kualitas Pelayanan Terhadap Minat Beli Ulang Pada Zero Outlet Singaraja - Ketut Mia Tiara; Trianadewi Trianadewi; Doni Tirtayasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study plans to determine the relationship between store layout, product variety, product design and service quality on repurchase interest at Zero Outlet Singaraja. The information checking strategy used in this exploration is Structural Equation Modeling (SEM) by looking at the differences in SEM, known as visual rendition 3.0 Partial Least Square (PLS). The consequence of this research shows that the store layout related to repurchase intention is positive and sig. where the result is 0.215 with t-count > 1.96. The impact of product variations on repurchase intention is positive and sig. where the result is 0.285 with a t-statistic value > 1.96, which is 2.769 and a large level of 0.002. The effect of product design on repurchase intention with positive values ​​and sig. where the coefficient is 0.235 and the t-statistic > 1.96, with a critical degree of 0.049 < 0.050. The effect of service quality on repurchase interest is positive and sig. where the coefficient is 0.203 and the t statistic is 2.147 with a standard t table value of 1.96 with sig. 0.032 < 0.050. Keywords : Store Layout, Product Variation, Product Design, Service Quality, Repurchase Interest